Somatoform disorders among children and adolescents in a tertiary hospital - Das, Anupam; Matin, Md Abdul; Ahmed, Sultanuddin; Ahmed, Md Shameem; Dey, Proshenjeet (KYAMC Journal, 2018)
Background: Somatoform disorders are common problem among children and adolescents. As children's verbal skills are relatively poorly developed to express their psychological problem, it is not surprising that they display somatic symptoms in response to life stresses. Objectives: The study aimed to explore the difference of somatoform disorders and symptoms between boys and girls the causal association of psychosocial factors. Materials & Methods: This is a cross-sectional descriptive study conducted at weekly Child Psychiatry Clinic of Psychiatry OPD and Pediatrics OPD in Bangabandhu Sheikh Mujib Medical University (BSMMU) of 6-16 years' age group from June to December' 2003. Total 450 respondents, 350 from Pediatric OPD & 100 from Child Psychiatry Clinic of Psychiatry OPD, were included in this study. Results: No significant gender difference was found in the diagnostic categories of somatoform disorders. Both boys and girls reported higher rates of undifferentiated somatoform disorders, 33.33% and 37.50% respectively. Abnormal psychosocial factors were found in majority of the cases and the most common was parental overprotection (26.42%). Overall, associated abnormal psychosocial situations were significantly higher among girls than that of boys (P<0.01). It was also revealed that higher rate of abnormal psychosocial factors was found to have causal relationship of higher rate of somatoform disorders among girls than that of boys. Conclusion: Findings suggested that somatoform disorders in children and adolescents were frequent in clinical settings and more in girls than that of boys due to more associated abnormal psychosocial situations among girls. KYAMC Journal Vol. 9, No.-2, July 2018, Page 69-72